State and Development Guidelines in Subjective Well-being of students in Guangxi Vocational University of Agriculture - Han Xu; Intarasompun Wichian; Punchatree Nuttamon (SHS Web of Conferences, 2024)
With the continuous development of the global economy, the transformation of social structure continues to accelerate, people’s living conditions gradually improve, and the demand level of college students continues to increase. However, due to the relative shortage of resources and the intensification of social competition, the pressure of college students has greatly increased. All of this All have a great impact on the happiness of college students.This article uses questionnaires and interviews to study the current situation of subjective well-being among students at Guangxi Agricultural Vocational University, and to provide guidelines for the development of subjective well-being among students at Guangxi Agricultural Vocational University.The research results show that the subjective well-being of students at Guangxi Agricultural Vocational University is generally at a high level. From the three dimensions that affect subjective well-being, self-health factors have the greatest impact, followed by family factors, and school factors have the least impact.The development guidelines proposed based on the above results are as follows: 1. Schools can help students by establishing mental health consulting agencies for college students, providing relevant mental health courses and face-to-face communication between teachers and students, thereby improving students’ subjective well-being. 2. Institutionalized guarantees are needed: A clear system should be established to ensure the improvement of students’ happiness and mental health education. 3. Disadvantages of improving students’ subjective well-being: First, the school’s hardware facilities can better help students build satisfaction with the school, thereby improving their sense of well-being. Secondly, there is room for improvement in helping students solve practical difficulties, such as timely intervention in students’ employment pressure and teachers’ timely intervention in students’ psychological problems. 4. Schools should organize relevant extracurricular activities to improve students’ subjective well-being. 5. Establishing positions dedicated to managing students, such as counselor positions, will help understand and solve students’ psychological problems. 6. Regular visits to students’ parents can help to gain an in-depth understanding of students’ family life and discover some hidden psychological conditions.